CONTINUOUS LIFELONG LEARNING AS A PRACTICE OF «SELF-CARE» - Natalia N. Balashova; Elena A. Klenina; Arkady E. Peskov (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The relevance of the presented topic should be associated with the existential situation characterized by the active development of the information society and its transition to a knowledge society, in which the values ​​associated with self-education and self-development of the individual prevail. Therefore, the strategy of continuous learning «throughout life» is in demand, allowing to satisfy the needs of the individual for self-development and self-improvement.